Soft magnetic powder and its manufacturing method, coil component using soft magnetic powder, and manufacturing method for magnetic material using soft magnetic powder

The production of soft magnetic powder with an insulating film containing insulating metal oxide and iron components addresses the challenge of achieving high permeability and resistance, improving performance in high-frequency applications.

JP7622769B2Active Publication Date: 2025-01-28MURATA MFG CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023062912
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-29
Filing Date
2023-04-07
Publication Date
2025-01-28
Estimated Expiration
2040-07-28

AI Technical Summary

Technical Problem

Existing magnetic materials face challenges in achieving high permeability and high electrical resistance, particularly in applications requiring high-frequency magnetic characteristics, due to difficulties in insulation treatment on metal magnetic bodies.

Method used

A method of producing soft magnetic powder with an insulating film containing insulating metal oxide and iron components buried within, formed by mixing core materials with iron salt, metal alcohoxide, water-soluble polymer, and surfactant, followed by drying to create a slurry with an insulating film covering the core.

Benefits of technology

The resulting soft magnetic powder achieves high permeability and high electrical resistance, reducing magnetic loss and enhancing performance in high-frequency applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007622769000002
    Figure 0007622769000002
  • Figure 0007622769000003
    Figure 0007622769000003
  • Figure 0007622769000004
    Figure 0007622769000004
Patent Text Reader

Abstract

To provide soft magnetic powder having high magnetic permeability and high electric resistance and a method for producing the same, a coil component using the soft magnetic powder, and a magnetic material using the soft magnetic powder.SOLUTION: Soft magnetic powder comprises a core composed of a soft magnetic metal material and an insulation film coating a surface of the core. The insulation film contains insulation metal oxide and an iron component. The iron component is buried in the insulation film.SELECTED DRAWING: Figure 1d
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic powder and a method for producing the same, a coil component containing the soft magnetic powder, and a method for producing a magnetic material using the soft magnetic powder. [Background technology]

[0002] There is a demand for magnetic materials with high electrical resistance as magnetic materials used in magnetic components such as coil components. For example, Patent Document 1 describes a magnetic material powder that is characterized by being produced by adding metal powder to a solution containing at least one type of metal alkoxide, dispersing the mixture uniformly, adding distilled water to the solution to hydrolyze the metal alkoxide, adsorbing the hydroxide onto the surface of the metal powder, and filtering, drying, and heating the powder. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 9-125111 Summary of the Invention [Problem to be solved by the invention]

[0004] As electrical equipment becomes smaller, there is a demand for smaller electronic components. Metal magnetic bodies have better DC superposition characteristics than ferrite, and are therefore useful for miniaturizing electronic components. When using metal magnetic bodies in electronic components such as coil components, the surface of the metal magnetic body may be subjected to an insulating treatment in order to ensure insulation and reduce magnetic loss (core loss). However, the present inventor has found that it is difficult to increase the magnetic permeability when the surface of the metal magnetic body is subjected to an insulating treatment. According to the inventor's investigation, this problem tends to be particularly prominent in applications requiring high-frequency magnetic properties.

[0005] An object of the present invention is to provide a soft magnetic powder having high magnetic permeability and high electrical resistance and a method for producing the same, a coil component using the soft magnetic powder, and a magnetic material using the soft magnetic powder. [Means for solving the problem]

[0006] As a result of intensive research into solving the above problems, the inventors discovered that by introducing an iron component into the insulating film that covers the surface of a core made of a soft magnetic metal material, a soft magnetic powder having higher magnetic permeability and higher electrical resistance can be obtained, and thus completed the present invention.

[0007] According to one aspect of the present invention, a core made of a soft magnetic metal material; An insulating film that covers the surface of the core; A soft magnetic powder comprising: A soft magnetic powder is provided in which the insulating film contains an insulating metal oxide and an iron component, the iron component being embedded in the insulating film.

[0008] According to one aspect of the present invention, a core made of a soft magnetic metal material, an iron salt, a metal alkoxide, and at least one selected from the group consisting of a water-soluble polymer and a surfactant are mixed in a solvent to obtain a slurry; drying the slurry to obtain a soft magnetic powder having a core and an insulating film covering a surface of the core; A method for producing a soft magnetic powder is provided, comprising:

[0009] According to one aspect of the present invention, a magnetic core including the above-mentioned soft magnetic powder and a binder; Coil conductor and A coil component is provided, comprising:

[0010] According to one aspect of the present invention, the soft magnetic powder is molded to obtain a molded body, heat-treating the compact to obtain a magnetic material; A method for producing a magnetic material is provided, comprising: Effect of the Invention

[0011] The soft magnetic powder according to the present invention can achieve high magnetic permeability and high electrical resistance. The manufacturing method of the soft magnetic powder according to the present invention can manufacture soft magnetic powder having high magnetic permeability and high electrical resistance. The coil component according to the present invention can be made of a magnetic material having high magnetic permeability and high electrical resistance. The manufacturing method of the magnetic material according to the present invention can manufacture a magnetic material having high magnetic permeability and high electrical resistance. [Brief description of the drawings]

[0012] [Figure 1a] 1 is a STEM-EDX analysis result (C (carbon) element mapping result) of a cross section of a soft magnetic powder according to an embodiment of the present invention. [Figure 1b] 2 is a STEM-EDX analysis result (mapping result of O (oxygen) element) of a cross section of the soft magnetic powder according to the embodiment of the present invention. [Figure 1c] 2 is a STEM-EDX analysis result (Si (silicon) element mapping result) of a cross section of a soft magnetic powder according to an embodiment of the present invention. [Figure 1d] 1 is a STEM-EDX analysis result (mapping result of Fe (iron) element) of a cross section of a soft magnetic powder according to an embodiment of the present invention. [Figure 2a] 1 is a TEM image of a cross section of the soft magnetic powder according to the first embodiment of the present invention. [Figure 2b] 1 is a TEM image of a cross section of the soft magnetic powder according to the first embodiment of the present invention. [Diagram 3] 5A and 5B are diagrams illustrating a coil component according to a second embodiment of the present invention. [Figure 4a] FIG. 11 is a perspective view illustrating a coil component according to a third embodiment of the present invention. [Figure 4b] FIG. 11 is an exploded perspective view showing a schematic diagram of an element body constituting a coil component according to a third embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [First embodiment] The soft magnetic powder according to the first embodiment of the present invention will be described below. The soft magnetic powder according to this embodiment has a core made of a soft magnetic metal material and an insulating film covering the surface of the core. In this specification, whether a film is an "insulating film" can be determined based on volume resistivity. For example, a high resistance resistivity meter (Hiresta (registered trademark)-UX MCP-HT800) manufactured by Mitsubishi Chemical Analytech Co., Ltd. is used as a powder resistance measuring device, and a volume resistivity of 10 g or more is measured under a load of 20 kN for a sample of soft magnetic powder having an insulating film. 6 In the present specification, the term "insulating" means a film having a volume resistivity of 10 6 This means that the resistance is Ωcm or more.

[0014] (core) The type of soft magnetic metal material constituting the core is not particularly limited and can be appropriately selected according to the application. The core is preferably composed of a soft magnetic metal material of Fe, Ni or Co. More specifically, the soft magnetic metal material constituting the core may be, for example, Fe, Fe-Ni alloy, Fe-Co alloy, Fe-Si alloy, Fe-Si-Cr alloy, Fe-Si-Al alloy or Fe-Si-B-Cr alloy. The average particle size of the core is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less. By making the average particle size of the core small, 20 μm or less, a soft magnetic powder of a small particle size can be obtained. If the soft magnetic powder has a small particle size, the core loss at high frequencies can be reduced as described later. The average particle size of the core can be obtained by polishing a cross section of the soft magnetic powder, obtaining an electron microscope image of the cross section, and analyzing the obtained image with image analysis software.

[0015] (insulating film) The insulating film covers the surface of the core. The insulating film contains an insulating metal oxide and an iron component, and the iron component is embedded in the insulating film. Here, the insulating metal oxide and the iron component are different substances. Furthermore, "embedded" means that the entire surface of the iron component is embedded in the insulating film, but some of the iron component may be present on the surface of the insulating film. When the iron component is in particulate form, "embedded" means that the entire particle surface of the iron component is covered with the components (insulating metal oxide and organic matter) that make up the insulating film, but some of the surfaces of the iron component particles may be exposed on the surface of the insulating film.

[0016] The average thickness of the insulating film is preferably 10 nm or more and 100 nm or less, more preferably 20 nm or more and 40 nm or less. When the average thickness of the insulating film is 10 nm or more, more preferably 20 nm or more, it becomes easier to embed the iron component that contributes to the improvement of the magnetic properties inside the insulating film. When the average thickness of the insulating film is 100 nm or less, more preferably 40 nm or less, the magnetic permeability of the soft magnetic powder can be further increased. The average thickness of the insulating film can be measured by the following procedure. First, the soft magnetic powder to be measured is embedded in resin and polished, and a sample for STEM-EDX observation is prepared by FIB (focused ion beam) processing. Using this sample, the cross section of the soft magnetic powder is photographed by STEM-EDX for three fields of view per particle, and the thickness of the insulating film is measured at four arbitrary points at equal intervals for each EDX image. The above-mentioned measurement is performed for three particles, and the average value obtained from the thicknesses of the insulating films measured at all points (3 fields of view x 4 points x 3 particles = 36 points) is defined as the "average thickness".

[0017] The soft magnetic powder according to this embodiment has a higher magnetic permeability and a higher electrical resistance because the surface of the core made of a soft magnetic metal material is covered with an insulating film and the iron component, which is a magnetic body, is embedded in the insulating film. In other words, according to the soft magnetic powder according to this embodiment, the insulating film contains the iron component, which is a magnetic body, so that the soft magnetic powder can be given insulation while suppressing the deterioration of the magnetic properties. Furthermore, since the surface of the core of the soft magnetic powder according to this embodiment is covered with an insulating film, when the soft magnetic powder according to this embodiment is molded to obtain a magnetic material, the contact between the cores of the soft magnetic powder is inhibited, and the magnetic loss of the magnetic material can be further reduced.

[0018] The above-mentioned effects of improving the magnetic properties and increasing the electrical resistance are particularly useful in applications requiring high-frequency magnetic properties. As the switching frequency of DC / DC converters and the like becomes higher, inductors with reduced core loss due to high-frequency switching are required. By using soft magnetic powder with a small particle size as the magnetic material, the core loss at high frequencies can be reduced. However, the soft magnetic powder tends to have a smaller magnetic permeability as the particle size becomes smaller. Therefore, it has been difficult to achieve both reduced core loss at high frequencies and high magnetic permeability. In contrast, the soft magnetic powder of this embodiment has an insulating film covering the surface of the core made of a soft magnetic metal material that contains a magnetic iron component, so that even if the particle size of the soft magnetic powder is small, a higher magnetic permeability can be achieved.

[0019] Whether or not iron components are embedded in the insulating film can be confirmed by STEM-EDX (scanning transmission electron microscope-energy dispersive X-ray analysis) in the following procedure. First, the soft magnetic powder to be measured is embedded in resin, polished, and a sample for STEM-EDX observation is prepared by FIB processing. Using this sample, elemental mapping of the cross section of the insulating film is performed by a STEM-EDX device. An example of the elemental mapping result is shown in Figures 1a to 1d. An FeSi alloy with Fe:Si=93.5:6.5 (weight ratio) was used for the core. Figure 1a shows the mapping result of C (carbon), Figure 1b shows the mapping result of O (oxygen), Figure 1c shows the mapping result of Si (silicon), and Figure 1d shows the mapping result of Fe (iron). From the elemental mapping results of Figures 1a to 1d, it can be seen that the area between the two dashed lines in the figures is the insulating film, and the area below the insulating film is the core. From Figure 1d, it can be seen that iron components are present in the insulating film. When iron elements are detected in the insulating film as shown in Figure 1d, it can be said that the iron components are embedded in the insulating film. As shown in Figure 1d and Figures 2a and 2b described later, the iron components may be distributed more in the vicinity of the core than in the vicinity of the surface of the insulating film. When analyzing the iron components in the insulating film of soft magnetic powder contained in electronic components, it is possible to confirm whether the iron components are embedded by performing the above-mentioned analysis on the cross section of the electronic component. As shown in Figures 1b and 1c, silicon elements and oxygen elements are detected at almost the same position, it can be confirmed that the insulating film contains silicon oxide as an insulating metal oxide.

[0020] After the insulating film is formed, it is possible to make the iron component present on the surface of the insulating film by separately adding the iron component to the surface of the insulating film, but it is preferable that the iron component is not present on the surface of the insulating film. That is, it is preferable that only components other than the iron component (for example, only insulating metal oxides and organic substances) are present on the surface of the insulating film. If the iron component is present on the surface of the insulating film, the electric resistance of the soft magnetic powder may decrease, and the moisture resistance may also decrease. The presence or absence of the iron component on the surface of the insulating film can be confirmed by XPS (X-ray photoelectron spectroscopy). If no peak derived from Fe is detected by XPS analysis of the insulating film, it can be determined that the iron component is not present on the surface of the insulating film.

[0021] The iron component is a component containing an iron element. The iron component is preferably an oxide containing iron, and more preferably iron oxide. In this case, the composition of the iron oxide (oxidation number of iron) is not particularly limited. The iron component may be an oxide having magnetism such as maghemite, hematite, or magnetite. Since iron oxide has a higher resistivity than metallic iron, if the iron component is iron oxide, the insulating property of the insulating film can be further improved. Whether the iron component is iron oxide or not can be confirmed by the element mapping described above. When the iron element and the oxygen element are detected at approximately the same position as shown in FIG. 1b and FIG. 1d, the iron component is considered to be iron oxide.

[0022] The insulating film preferably contains particles of iron components. In other words, the iron components preferably exist in the form of particles in the insulating film. The entire surface of the iron component particles is covered with the components (insulating metal oxide and organic matter) that make up the insulating film, and they exist dispersedly in the insulating film. Whether the iron components exist in the form of particles or not can be confirmed by the above-mentioned element mapping and a transmission electron microscope (TEM) image of the cross section of the insulating film. An example of a TEM image of the cross section of the insulating film is shown in Figures 2a and 2b. As shown in Figure 2b, the area in the TEM image where lattice fringes are observed corresponds to the particles of the iron components. The lattice fringes in the TEM image indicate the presence of crystals.

[0023] The average particle size of the iron component particles is preferably 5 nm or more and 20 nm or less. If the average particle size is 5 nm or more, the relative magnetic permeability of the soft magnetic powder can be further increased. If the average particle size is 20 nm or less, the iron component particles can be made smaller than the size of the magnetic domain, and magnetic loss can be further reduced. In other words, the insulating film preferably contains iron component nanoparticles (crystals with a particle size on the order of nanometers). The average particle size of the iron component particles can be determined based on a TEM image by the following procedure. In the TEM image, the major axis (longest diameter) and minor axis (shortest diameter) are measured for each of 10 iron component particles, and the average value of the major axis and minor axis is defined as the particle size of the particle. The average value of the particle sizes of the 10 particles determined in this manner is defined as the average particle size.

[0024] The content of the iron component in the insulating film, calculated from the ratio of the weight of Fe in the insulating film to the weight of the core, is, for example, 0.3% by weight to 5% by weight, preferably 0.5% by weight to 3% by weight. When the content of the iron component is 0.5% by weight or more, the magnetic permeability of the soft magnetic powder can be further increased. When the content of the iron component is 3% by weight or less, the electrical resistance can be further increased. The content of the iron component in the insulating film can be estimated from the amount of iron salt, which is the raw material of the iron component, charged.

[0025] The insulating metal oxide constituting the insulating film is preferably a hydrolyzate of a metal alkoxide. The insulating film may contain an organic substance as described later. An insulating film in which an insulating metal oxide with a high melting point and an organic substance with a low melting point are hybridized can be formed by utilizing a hydrolysis reaction of a metal alkoxide that can generate an insulating metal oxide in a low-temperature process. Details of the metal alkoxide will be described later. The insulating metal oxide is preferably at least one selected from the group consisting of titanium oxide, silicon oxide, aluminum oxide, and zirconium oxide. In addition, the insulating metal oxide is preferably amorphous.

[0026] The insulating film preferably further contains an organic substance. The organic substance is preferably at least one selected from the group consisting of water-soluble polymers and surfactants. As described below, the water-soluble polymers and surfactants function to assist the introduction of iron components into the insulating film when the insulating film is formed on the surface of the core. Details of the water-soluble polymers and surfactants will be described later.

[0027] The insulating film preferably contains at least one element selected from the group consisting of C, N and P. These elements are derived from the water-soluble polymer and / or surfactant.

[0028] In the insulating film, the insulating metal oxide and the organic matter (water-soluble polymer and / or surfactant) exist in a hybridized state (a state where they are uniformly mixed at the molecular level). Whether or not the insulating metal oxide and the organic matter are hybridized and the constituent elements of the organic matter can be confirmed by analyzing the insulating film using a Fourier transform infrared spectrophotometer (FT-IR) and checking the peak shift of the OH group in the obtained IR spectrum. The constituent elements of the organic matter can also be confirmed by analyzing the soft magnetic powder using gas chromatography-mass spectrometry (GC-MS) and checking the detected organic components.

[0029] Although a part of the core may be exposed on the surface of the soft magnetic powder without being covered with the insulating film, it is preferable that the entire surface of the core is covered with the insulating film. The average coverage rate of the insulating film on the soft magnetic powder is preferably 90% or more, more preferably 95% or more, even more preferably 99% or more, and particularly preferably 100%.

[0030] (Method of manufacturing soft magnetic powder) Next, a method for producing the soft magnetic powder according to the first embodiment will be described. The method for producing the soft magnetic powder according to the first embodiment includes mixing a core made of a soft magnetic metal material, an iron salt, a metal alkoxide, and at least one selected from the group consisting of a water-soluble polymer and a surfactant in a solvent to obtain a slurry, drying the slurry to obtain a soft magnetic powder having a core and an insulating film covering a surface of the core; Includes.

[0031] (Preparation of Slurry) First, a core made of a soft magnetic metal material, an iron salt, a metal alkoxide, and at least one selected from the group consisting of a water-soluble polymer and a surfactant are mixed in a solvent to obtain a slurry.

[0032] The type and average particle size of the soft magnetic metal material constituting the core are as described above. It is acceptable to consider that the average particle size of the raw core and the average particle size of the core in the obtained soft magnetic powder are substantially the same. The average particle size of the raw core can be measured using a laser diffraction type particle size distribution measuring device or the like. The average particle size of the raw core can be expressed as a volume-based median diameter.

[0033] (iron salts) The iron salt is a raw material for the iron component contained in the insulating film. The iron salt can be any iron salt, such as inorganic salts such as iron chloride, iron sulfate, iron nitrate, iron phosphate, and iron nitrite, and their hydrates, organic salts such as iron oxalate, iron acetate, iron succinate, and iron malate, and complex salts. When alcohol is used as the solvent, the iron salt is preferably soluble in alcohol. Specifically, the iron salt is preferably at least one selected from the group consisting of iron chloride, iron nitrate, and their hydrates. As the iron salt, one type of iron salt may be used alone, or two or more types of iron salts may be used in combination. The iron salt is preferably added at a ratio of 0.1% by weight to 20% by weight based on the weight of the core.

[0034] (Metal alkoxide) Metal alkoxides are the raw material for the insulating metal oxide contained in the insulating film. The metal alkoxides are hydrolyzed in the slurry to form an insulating film containing an insulating metal oxide on the surface of the core. By utilizing the hydrolysis reaction of the metal alkoxides, it is possible to form an insulating film that is a hybrid of an insulating metal oxide and an organic material (a water-soluble polymer and / or a surfactant).

[0035] Metal alkoxides have the chemical formula M(OR) x (M: metal element, OR: alkoxy group). The metal species M constituting the metal alkoxide may be at least one selected from the group consisting of Li, Na, Mg, Al, Si, K, Ca, Ti, Cu, Sr, Y, Zr, Ba, Ce, Ta and Bi. Among them, the metal alkoxide is preferably at least one alkoxide selected from the group consisting of Si, Ti, Al and Zr, and more preferably Si. When the metal alkoxide is at least one alkoxide selected from the group consisting of Si, Ti, Al and Zr, an insulating metal oxide having higher strength and higher resistivity can be formed. Furthermore, when the metal species M is Si, the metal alkoxide (Si(OR)4) becomes more chemically stable, making it easier to handle during production.

[0036] The alkoxy group OR constituting the metal alkoxide is not particularly limited, and may be, for example, an alkoxy group having 10 or less carbon atoms, particularly 5 or less, more particularly 3 or less. The smaller the carbon number, the easier the hydrolysis reaction can proceed. The alkoxy group is preferably at least one selected from the group consisting of, for example, a methoxy group, an ethoxy group, and a propoxy group. Specifically, the metal alkoxide is preferably at least one selected from the group consisting of tetraethyl orthosilicate, titanium tetraisopropoxide, zirconium-n-butoxide, and aluminum isopropoxide.

[0037] In the manufacturing method according to the present embodiment, one kind of metal alkoxide may be used, or two or more kinds of metal alkoxides may be used in combination. The metal alkoxide is preferably added in a ratio of 0.1% by weight to 5% by weight, calculated as the insulating metal oxide to be obtained, relative to the weight of the core.

[0038] (Water-soluble polymers and surfactants) The water-soluble polymer and surfactant act to help introduce the iron component into the insulating film. The water-soluble polymer and surfactant have a ligand capable of forming a complex with Fe ions and a proton-accepting group and / or a proton-donating group capable of forming a hydrogen bond with the hydrolysate of the metal alkoxide. Therefore, the water-soluble polymer and / or surfactant coordinately bonded to the Fe ion forms a hydrogen bond with the hydrolysate of the metal alkoxide, and the iron component is incorporated into the insulating film. As a ligand capable of forming a complex with the Fe ion, for example, a compound having a functional group with a lone electron pair capable of donating an electron to the vacant d orbital of the Fe ion can be used.

[0039] The water-soluble polymer may be any of anionic, cationic and nonionic, and may be, for example, at least one selected from the group consisting of polyethyleneimine, polyvinylpyrrolidone, polyethylene glycol, polyacrylic acid, carboxymethylcellulose, hydroxypropylcellulose, polyacrylamide, poly(2-methyl-2-oxazoline), polyvinyl alcohol and gelatin. Among them, the water-soluble polymer is preferably at least one selected from the group consisting of polyvinylpyrrolidone, polyvinyl alcohol, hydroxypropylcellulose, poly(2-methyl-2-oxazoline), polyethyleneimine, polyacrylic acid and carboxymethylcellulose.

[0040] The surfactant may be anionic, cationic, nonionic or amphoteric, and may be, for example, at least one selected from the group consisting of fatty acid salts, α-sulfo fatty acid ester salts, alkylbenzene sulfonates, alkyl sulfates, alkyl ether sulfate ester salts, alkyl triethanolamine sulfates, fatty acid diethanolamides, polyoxyethylene alkyl ethers, polyoxyethylene alkyl phenyl ethers, alkyl trimethyl ammonium salts, dialkyl dimethyl ammonium chlorides, alkyl pyridinium chlorides, and alkyl carboxy betaines. Among these, the surfactant is preferably at least one selected from the group consisting of sodium polyoxyalkylene styryl phenyl ether phosphate, hexadecyl trimethyl ammonium bromide, and diethanolamide laurate.

[0041] As the organic material that forms a complex with Fe ions, one type of water-soluble polymer may be used alone, or two or more types of water-soluble polymers may be used in combination. Alternatively, as the organic material that forms a complex with Fe ions, one type of surfactant may be used alone, or two or more types of surfactants may be used in combination. Alternatively, as the organic material that forms a complex with Fe ions, one or more types of water-soluble polymers and one or more types of surfactants may be used in combination. The organic material that forms a complex with Fe ions is preferably added at a ratio of 0.1% by weight to 1% by weight based on the weight of the core.

[0042] (solvent) As the solvent, a solvent generally used in the sol-gel method can be appropriately used. The solvent preferably contains alcohol. When the solvent contains alcohol, for example, methanol, ethanol, etc. can be used as the alcohol.

[0043] (catalyst) In order to accelerate the hydrolysis rate of the metal alkoxide, a catalyst may be added as necessary. As the catalyst, for example, an acid catalyst such as hydrochloric acid, acetic acid, phosphoric acid, etc., a basic catalyst such as ammonia, sodium hydroxide, piperidine, etc., or a salt catalyst such as ammonium carbonate, ammonium acetate, etc. can be used. Among them, ammonia is preferable because it has low reactivity with the core and does not adversely affect the resistance value of the insulating film even if it remains in the insulating film.

[0044] The above-mentioned raw materials are mixed to obtain a slurry. Obtaining the slurry in this manner may include hydrolysis of the metal alkoxide. The mixing may be performed at room temperature, or may be performed while heating. The obtained slurry may be subjected to a process such as filtration and / or washing before drying, which will be described later. The filtration may be performed using a pressure filter such as a filter press, a vacuum filter such as a Nutsche filter, a centrifugal filter, or the like. The washing may be performed using, for example, acetone, or the like.

[0045] (Dry) Next, the slurry is dried to obtain a soft magnetic powder having cores and an insulating film covering the surfaces of the cores. Drying may be performed at room temperature or with heating.

[0046] The above-mentioned method can form an insulating film containing an insulating metal oxide and an iron component, with the iron component being embedded in the insulating film. The soft magnetic powder obtained by the above-mentioned method has such an insulating film and thus has higher magnetic permeability and higher electrical resistance.

[0047] The insulating metal oxide is preferably at least one oxide selected from the group consisting of Si, Al, Ti, and Zr. When the insulating metal oxide is at least one oxide selected from the group consisting of Si, Al, Ti, and Zr, the strength and resistivity of the insulating film can be further improved.

[0048] [Second embodiment] Next, a magnetic material and a coil component according to a second embodiment of the present invention will be described below.

[0049] The magnetic material according to the present embodiment includes the soft magnetic powder according to the embodiment of the present invention and a binder. As the binder, at least one selected from the group consisting of thermosetting resins such as epoxy resins, phenolic resins, and silicone resins, and low-melting glass can be used. The magnetic material according to the present embodiment can be manufactured by adding a binder to the soft magnetic powder, molding it into a predetermined shape, and curing it by heating as necessary. The molding can be performed, for example, by using a mold or by filling the injected part. The heating temperature can be appropriately set according to the curing temperature of the binder used. For example, when an epoxy resin is used as the binder, the epoxy resin can be cured by heating at a temperature of 150°C or more and 200°C or less. The magnetic material according to the present embodiment has a higher magnetic permeability and a higher electrical resistance.

[0050] FIG. 3 is a schematic diagram of a coil component according to a second embodiment. The coil component 1 shown in FIG. 3 includes a magnetic core 12 including a soft magnetic powder and a binder according to an embodiment of the present invention, and a coil conductor 11. The magnetic core 12 is made of a magnetic material including a soft magnetic powder and a binder according to an embodiment of the present invention. The coil conductor 11 is a conductor formed in a coil shape, and may be, for example, a conductor wire wound in an alpha-wound coil shape. For example, a copper wire or a silver wire can be used as the conductor wire. The coil conductor 11 may be formed by applying a conductor paste in a coil shape on a substrate. The coil conductor 11 may be formed by patterning a metal film in a coil shape on a substrate by etching or the like. In the coil component 1 according to this embodiment, the coil conductor 11 may be disposed in the magnetic core 12 as shown in FIG. 3, but the coil conductor 11 may be wound around the magnetic core 12. The coil component 1 according to this embodiment has a higher magnetic permeability and a higher electrical resistance.

[0051] In the coil component 1 shown in FIG. 3, the coil conductor 11 is embedded in a magnetic core (element) 12 containing soft magnetic powder and a binder. The winding ends 11A and 11B of the coil conductor 11 are electrically connected to terminal electrodes 13 formed on both ends of the magnetic core 12, respectively. The terminal electrodes 13 may be formed by applying a conductive paste, such as Ag paste or Cu paste, to the magnetic core. Alternatively, the terminal electrodes 13 may be formed by Ni sputtering, Ti sputtering, NiCr sputtering, or the like. Alternatively, the terminal electrodes 13 may be, for example, cap-shaped metal conductors. In this case, the cap-shaped metal conductors (terminal electrodes) 13 are fitted into both ends of the element 12, and the terminal electrodes 13 can be connected and fixed to the element 12 and the winding ends 11A and 11B using a conductive adhesive or the like. The terminal electrodes 13 may be a single layer, or may be a laminate of multiple layers.

[0052] An example of a method for manufacturing the coil component 1 according to the present embodiment will be described below. First, a soft magnetic powder and a binder are mixed to obtain a mixture. This mixture is formed into a sheet to obtain a magnetic sheet. After embedding the coil conductor 11 in this magnetic sheet, the magnetic sheet is cut to a predetermined size and heated to a predetermined temperature to harden the binder, thereby obtaining a magnetic core 12 with the coil conductor 11 disposed therein. The coil component 1 can be obtained by forming a terminal electrode 13 on this magnetic core 12. Alternatively, the magnetic core 12 with the coil conductor 11 disposed therein can also be produced by the following method. First, a coil conductor pattern is formed on a magnetic sheet obtained by molding a mixture of a coil soft magnetic powder and a binder. A predetermined number of magnetic sheets on which the coil conductor pattern is formed are stacked to obtain a laminate. The laminate is cut to a predetermined size, and then heated to a predetermined temperature to harden the binder, thereby obtaining a magnetic core 12 with the coil conductor 11 disposed therein. The coil component 1 can be obtained by forming a terminal electrode 13 on this magnetic core 12.

[0053] [Third embodiment] Next, a magnetic material and a coil component according to a third embodiment of the present invention will be described below.

[0054] The manufacturing method of the magnetic material according to the present embodiment includes forming the soft magnetic powder according to the embodiment of the present invention to obtain a molded body, and heat-treating the molded body to obtain a magnetic material. First, a binder such as PVA (polyvinyl alcohol) is added to the soft magnetic powder and mixed to obtain a magnetic paste. This magnetic paste is formed by a doctor blade method or the like to obtain a molded body. This molded body is heat-treated (fired) at a predetermined temperature in an air atmosphere to obtain a magnetic material. The heat treatment temperature is preferably, for example, about 200°C or higher and 850°C or lower. The cores in the magnetic material according to the present embodiment are preferably bonded to each other by oxide films that cover the surfaces of each core. The magnetic material obtained in this manner has a higher magnetic permeability and a higher electrical resistance.

[0055] 4a and 4b show an example of a coil component made of the magnetic material according to the present embodiment. FIG. 4a is a perspective view of the coil component 2, and FIG. 4b is an exploded perspective view of an element body 22 constituting the coil component 2. The coil component 2 shown in FIG. 4a includes an element body 22 and a coil conductor disposed inside the element body 22. The element body 22 is made of a magnetic material manufactured using the soft magnetic powder according to the embodiment of the present invention. As shown in FIG. 4b, the coil conductor may be made of coil conductor patterns 21A to 21C, and the element body 22 may be made of magnetic layers 22A to 22D. The coil component 2 may further include a terminal electrode 23. The coil component 2 according to the present embodiment has a higher magnetic permeability and a higher electrical resistance.

[0056] An example of a method for manufacturing the coil component 2 according to this embodiment will be described below. First, a binder such as PVA is added to and mixed with soft magnetic powder to obtain a magnetic paste for forming the magnetic layers 22A to 22D. A conductor paste such as Ag paste for forming the coil conductor patterns 21A to 21C is also prepared separately. The magnetic paste and the conductor paste are printed alternately in layers to obtain a molded body. The molded body is subjected to a binder removal process at a predetermined temperature in the atmosphere and then a heat treatment at a predetermined temperature to obtain the element body 22. Terminal electrodes 23 are formed on both ends of the obtained element body 22. The terminal electrodes 23 can be formed, for example, by applying a conductor paste such as Ag paste for the terminal electrodes 13 to both ends of the element body 22, baking the conductor paste, and then plating the conductor paste. EXAMPLES

[0057] Example 1 The soft magnetic powder of Example 1 was prepared by the procedure described below. In Example 1, the core was FeSi alloy powder (Fe:Si=93.5:6.5 (weight ratio)) with an average particle size (volume-based median diameter) of 5 μm prepared by water atomization method, iron chloride tetrahydrate was used as the iron salt, tetraethyl orthosilicate was used as the metal alkoxide, polyvinylpyrrolidone K30 was used as the water-soluble polymer, ethanol was used as the solvent, and ammonia was used as the basic catalyst. 10 g of 9 wt% ammonia aqueous solution and 50 g of FeSi alloy powder were added to 14.2 g of ethanol. Polyvinylpyrrolidone K30 was added to the ethanol to which the ammonia aqueous solution and FeSi alloy powder were added, so that the amount of polyvinylpyrrolidone K30 was 0.5 wt% relative to the weight of the FeSi alloy powder, and iron chloride tetrahydrate was added to the ethanol to which the ammonia aqueous solution and FeSi alloy powder were added, and the mixture was stirred to obtain a mixed liquid. Tetraethyl orthosilicate was weighed out so as to be 3% by weight in terms of SiO2 relative to the weight of the FeSi alloy powder, and was dropped into the mixed liquid. The mixed liquid after the dropping was stirred and mixed for 60 minutes to obtain a slurry. This slurry was filtered, washed with acetone, and then dried at 60°C to obtain the soft magnetic powder of Example 1. Almost no iron was detected in the filtrate after filtration or in the washing liquid after washing.

[0058] Example 2 A soft magnetic powder of Example 2 was prepared in the same manner as in Example 1, except that polyvinylpyrrolidone K30 was added so as to be 0.25% by weight based on the weight of the FeSi alloy powder (Fe:Si=93.5:6.5 (weight ratio)).

[0059] Example 3 A soft magnetic powder of Example 3 was prepared in the same manner as in Example 1, except that iron chloride tetrahydrate was added so as to be 1.7% by weight based on the weight of the FeSi alloy powder.

[0060] (Examples 4 to 6) Soft magnetic powders of Examples 4 to 6 were prepared in the same manner as in Example 1, except that titanium tetraisopropoxide, zirconium-n-butoxide and aluminum isopropoxide were used as the metal alkoxides instead of tetraethyl orthosilicate.

[0061] (Examples 7 to 12) The soft magnetic powders of Examples 7 to 12 were prepared in the same manner as in Example 1, except that polyvinyl alcohol, hydroxypropyl cellulose, poly(2-methyl-2-oxazoline), sodium polyoxyalkylene styryl phenyl ether phosphate, hexadecyltrimethylammonium bromide and lauric acid diethanolamide were used instead of polyvinylpyrrolidone K30, respectively.

[0062] (Example 13) A soft magnetic powder of Example 13 was prepared in the same manner as in Example 1, except that iron nitrate nonahydrate was used as the iron salt instead of iron chloride tetrahydrate.

[0063] Comparative Example 1 A soft magnetic powder of Comparative Example 1 was prepared in the same manner as in Example 1, except that no water-soluble polymer was added.

[0064] Comparative Example 2 A soft magnetic powder of Comparative Example 2 was prepared in the same manner as in Example 1, except that no iron salt was added.

[0065] Comparative Example 3 A soft magnetic powder of Comparative Example 3 was prepared in the same manner as in Example 1, except that no metal alkoxide was added.

[0066] (Iron component analysis) The average particle size of the iron component present in the insulating film and the presence or absence of the iron component on the insulating film surface were measured for each of the soft magnetic powders of Examples 1 to 13 and Comparative Examples 1 to 3 by the procedure described below. First, the soft magnetic powder to be measured was embedded in resin and polished, and a sample for STEM-EDX observation was prepared by FIB (focused ion beam) processing. Using this sample, elemental mapping of the cross section of the insulating film was performed by a STEM-EDX device. The STEM used was JEM-2000FS manufactured by JEOL Ltd., and the EDX device used was NoranSystem7. As a result of elemental mapping, it was confirmed that the iron component was embedded in the insulating film for the soft magnetic powders of Examples 1 to 13. As a representative example, the elemental mapping result of Example 1 is shown in Figures 1a to 1d. As shown in Figures 1b and 1d, the iron element and the oxygen element are detected at almost the same position, so it can be assumed that the iron component is iron oxide. On the other hand, no iron component was observed embedded in the insulating film for the soft magnetic powders of Comparative Examples 1 to 3. In Figure 1a, C (carbon) element originating from organic matter is detected in the insulating film. In addition, an oxide film containing iron was detected near the boundary between the insulating film and the core in Fig. 1d. This is presumably due to an oxide film formed on the surface of the FeSi alloy powder (Fe:Si=93.5:6.5 (weight ratio)) used as the core in the process of fabricating the powder by water atomization.

[0067] For the soft magnetic powders of Examples 1 to 13 in which the presence of iron components buried in the insulating film was confirmed, images of the cross section of the insulating film were taken using a TEM. As a representative example, TEM images of the cross section of the insulating film of Example 1 are shown in Figures 2a and 2b. In Figures 2a and 2b, lattice fringes corresponding to the iron component particles were observed. Based on the obtained TEM images, the average particle size of the iron component particles buried in the insulating film was determined by the following procedure. For each of the 10 iron component particles, the major axis (longest diameter) and minor axis (shortest diameter) were measured, and the average value of the major axis and minor axis was taken as the particle size of the particle. The average value of the particle sizes of the five particles was taken as the average particle size. The results are shown in Table 1. Table 1 also shows the content of the iron component buried in the insulating film (excluding the iron component on the surface of the insulating film). The content of the iron component (wt%) was calculated from the ratio of the weight of Fe in the insulating film to the weight of the core. The values ​​shown in Table 1 are values ​​estimated from the amount of iron salt, which is the raw material of the iron component, charged, assuming that all of the iron in the iron salt was taken into the insulating film. For the soft magnetic powders of Comparative Examples 1 to 3 in which no iron component was observed embedded in the insulating film in elemental mapping of the cross section of the insulating film by a STEM-EDX device, the iron content in Table 1 was recorded as 0 wt %.

[0068] For each of the soft magnetic powders of Examples 1 to 13 and Comparative Examples 1 to 3, XPS analysis was performed to confirm whether or not iron components were present on the surface of the insulating film. The XPS analysis was performed using a VersaProbe manufactured by ULVAC-PHI, Inc. As a result of the XPS analysis, when an Fe peak was detected, it was determined that iron components were present on the surface of the insulating film, and this is indicated by "present" in Table 1. When an Fe peak was not detected, it was determined that iron components were not present on the surface of the insulating film, and this is indicated by "absent" in Table 1.

[0069] (Toroidal ring manufacturing) Using the soft magnetic powders of Examples 1 to 13 and Comparative Examples 1 to 3, toroidal rings were produced in the following manner. The soft magnetic powders were mixed with 3% by weight of silicone resin relative to the weight of the soft magnetic powder to obtain granules. The granules were heated and molded using a metal mold, and then hardened to obtain toroidal rings.

[0070] (Measurement of resistivity) A voltage of 10 V was applied for 5 seconds to each of the toroidal rings produced using the soft magnetic powders of Examples 1 to 13 and Comparative Examples 1 to 3 to measure the resistivity of the toroidal ring. The resistivity was measured using a digital electrometer (Advantest R8340A ULTRA HIGH RESISTANCE METER) manufactured by Advantest Corporation. The results are shown in Table 1.

[0071] (Measurement of relative permeability) The relative permeability at 1 MHz was measured for each of the toroidal rings produced using the soft magnetic powders of Examples 1 to 13 and Comparative Examples 1 to 3. The relative permeability was measured using an impedance analyzer (Agilent E4991A RF) manufactured by Agilent Technologies. The results are shown in Table 1.

[0072] [Table 1]

[0073] As shown in Table 1, in the soft magnetic powders of Examples 1 to 13, nanoparticles of iron components embedded in the insulating film were detected. In addition, in the soft magnetic powders of Examples 1 to 13, no components were detected on the surface of the insulating film. In contrast, in the soft magnetic powder of Comparative Example 1, to which no water-soluble polymer or surfactant was added, no iron components embedded in the insulating film were detected. In the soft magnetic powder of Comparative Example 1, iron components were detected on the surface of the insulating film. In the soft magnetic powder of Comparative Example 2, to which no iron salt was added, no iron components embedded in the insulating film were detected. In the soft magnetic powder of Comparative Example 3, to which no metal alkoxide was added, no iron components embedded in the insulating film were detected. In the soft magnetic powder of Comparative Example 1, iron components were detected on the surface of the insulating film.

[0074] As shown in Table 1, the soft magnetic powders of Examples 1 to 13 had a magnetic flux density of 9.80 × 10 11The soft magnetic powder of Comparative Example 1, to which no water-soluble polymer or surfactant was added, exhibited a low resistivity and a low relative permeability compared to the soft magnetic powders of Examples 1 to 13. The soft magnetic powder of Comparative Example 2, to which no iron salt was added, exhibited a low relative permeability compared to the soft magnetic powders of Examples 1 to 13. The soft magnetic powder of Comparative Example 3, to which no metal alkoxide was added, exhibited a low resistivity and a low relative permeability compared to the soft magnetic powders of Examples 1 to 13.

[0075] The present invention includes the following aspects, but is not limited to these aspects. (Aspect 1) A core made of a soft magnetic metal material; An insulating film that covers the surface of the core; A soft magnetic powder comprising: The insulating film contains an insulating metal oxide and an iron component, and the iron component is embedded in the insulating film. (Aspect 2) 2. The soft magnetic powder according to embodiment 1, wherein the iron component is iron oxide. (Aspect 3) 3. The soft magnetic powder according to claim 1 or 2, wherein the insulating film contains particles of an iron component. (Aspect 4) The soft magnetic powder according to any one of aspects 1 to 3, wherein the average particle size of the iron component is 5 nm or more and 20 nm or less. (Aspect 5) The soft magnetic powder according to any one of aspects 1 to 4, wherein the insulating metal oxide is a hydrolysate of a metal alkoxide. (Aspect 6) 6. The soft magnetic powder according to any one of aspects 1 to 5, wherein the insulating film further contains an organic substance. (Aspect 7) 7. The soft magnetic powder according to embodiment 6, wherein the organic substance is at least one selected from the group consisting of a water-soluble polymer and a surfactant. (Aspect 8) The soft magnetic powder according to any one of aspects 1 to 7, wherein the insulating film contains at least one element selected from the group consisting of C, N and P. (Aspect 9) The soft magnetic powder according to any one of Aspects 1 to 8, wherein the insulating metal oxide is at least one selected from the group consisting of titanium oxide, silicon oxide, aluminum oxide, and zirconium oxide. (Aspect 10) 12. The soft magnetic powder according to any one of Aspects 1 to 11, wherein the core is made of an Fe-, Ni-, or Co-based soft magnetic metal material. (Aspect 11) 11. The soft magnetic powder according to any one of aspects 1 to 10, wherein no iron component is present on the surface of the insulating film. (Aspect 12) Further comprising an iron-containing oxide film; 12. The soft magnetic powder according to any one of aspects 1 to 11, wherein the iron-containing oxide film is formed in the vicinity of the boundary between the insulating film and the core. (Aspect 13) A core made of a soft magnetic metal material, an iron salt, a metal alkoxide, and at least one selected from the group consisting of a water-soluble polymer and a surfactant are mixed in a solvent to obtain a slurry; drying the slurry to obtain a soft magnetic powder having a core and an insulating film covering a surface of the core; A method for producing a soft magnetic powder comprising the steps of: (Aspect 14) 14. The method for producing a soft magnetic powder according to embodiment 13, wherein obtaining a slurry comprises hydrolyzing a metal alkoxide. (Aspect 15) 15. The method for producing a soft magnetic powder according to embodiment 13 or 14, wherein the iron salt is soluble in alcohol. (Aspect 16) 16. The method for producing a soft magnetic powder according to claim 15, wherein the iron salt is at least one selected from the group consisting of iron chloride, iron nitrate, and hydrates thereof. (Aspect 17) 17. The method for producing a soft magnetic powder according to any one of aspects 13 to 16, wherein the water-soluble polymer and the surfactant have a ligand capable of forming a complex with Fe ions. (Aspect 18) A method for producing a soft magnetic powder according to aspect 17, wherein the water-soluble polymer is at least one selected from the group consisting of polyvinylpyrrolidone, polyvinyl alcohol, hydroxypropyl cellulose, poly(2-methyl-2-oxazoline), polyethyleneimine, polyacrylic acid, and carboxymethyl cellulose. (Aspect 19) 19. The method for producing a soft magnetic powder according to aspect 17 or 18, wherein the surfactant is at least one selected from the group consisting of sodium polyoxyalkylene styryl phenyl ether phosphate, hexadecyltrimethylammonium bromide, and lauric acid diethanolamide. (Aspect 20) 20. The method for producing a soft magnetic powder according to any one of aspects 13 to 19, wherein the metal alkoxide is at least one alkoxide selected from the group consisting of Si, Al, Ti, and Zr. (Aspect 21) 21. The method for producing a soft magnetic powder according to any one of aspects 13 to 20, wherein the solvent contains an alcohol. (Aspect 22) A magnetic core including the soft magnetic powder according to any one of aspects 1 to 12 and a resin; A coil conductor disposed inside the body; Including, the coil components. (Aspect 23) Molding the soft magnetic powder according to any one of aspects 1 to 12 to obtain a molded body; heat-treating the compact to obtain a magnetic material; A method for producing a magnetic material, comprising:

[0076] Although one embodiment of the present invention has been described above, it is merely a typical example within the scope of application of the present invention. Therefore, it will be easily understood by those skilled in the art that the present invention is not limited to this embodiment and that various modifications can be made. [Industrial Applicability]

[0077] The soft magnetic powder and its manufacturing method according to the present invention, the coil component using the soft magnetic powder, and the magnetic material using the soft magnetic powder can achieve higher magnetic permeability and higher electrical resistance, and therefore can be suitably used in a wide range of applications such as high frequency applications. [Explanation of symbols]

[0078] 1, 2 Coil parts 11 Coil conductor 11A, 11B winding end 12, 22 Body (magnetic core) 13, 23 terminal electrode 21A, 21B, 21C Coil conductor patterns 22A, 22B, 22C, 22D magnetic layer

Claims

1. A core made of a soft magnetic metal material; an insulating film covering the surface of the core; A soft magnetic powder comprising: The insulating film contains an insulating metal oxide and an iron component, the iron component includes one embedded in the insulating film, the insulating film contains particles of the iron component, and the insulating film encapsulates the iron component, which is a magnetic body.

2. 2. The soft magnetic powder according to claim 1, wherein the iron component is iron oxide.

3. 3. The soft magnetic powder according to claim 1, wherein the average particle size of the iron component particles is 5 nm or more and 20 nm or less.

4. The soft magnetic powder according to any one of claims 1 to 3, wherein the insulating metal oxide is a hydrolysate of a metal alkoxide.

5. The soft magnetic powder according to any one of claims 1 to 4, wherein the insulating film further contains an organic substance.

6. The soft magnetic powder according to claim 5 , wherein the organic matter is at least one selected from the group consisting of water-soluble polymers and surfactants.

7. The soft magnetic powder according to any one of claims 1 to 6, wherein the insulating film contains at least one element selected from the group consisting of C, N and P.

8. The soft magnetic powder according to any one of claims 1 to 7, wherein the insulating metal oxide is at least one selected from the group consisting of titanium oxide, silicon oxide, aluminum oxide and zirconium oxide.

9. The soft magnetic powder according to any one of claims 1 to 8, wherein the core is made of an Fe-based, Ni-based or Co-based soft magnetic metal material.

10. The soft magnetic powder according to any one of claims 1 to 9, wherein the iron component is not present on the surface of the insulating film.

11. Further comprising an iron-containing oxide film; The soft magnetic powder according to any one of claims 1 to 10, wherein the iron-containing oxide film is formed in the vicinity of the boundary between the insulating film and the core.

12. The soft magnetic powder according to any one of claims 1 to 11, wherein the entire surface of the iron component particles is covered with the insulating metal oxide and organic matter of the insulating film.

13. The soft magnetic powder according to any one of claims 1 to 12, wherein particles of the iron component are dispersed in the insulating film.

14. A core made of a soft magnetic metal material, an iron salt, a metal alkoxide, and at least one selected from the group consisting of a water-soluble polymer and a surfactant are mixed in a solvent to obtain a slurry; drying the slurry to obtain a soft magnetic powder having the core and an insulating film covering a surface of the core; A method for producing a soft magnetic powder comprising the steps of:

15. The method for producing a soft magnetic powder according to claim 14, wherein obtaining the slurry includes hydrolyzing the metal alkoxide.

16. The method for producing a soft magnetic powder according to claim 14 or 15, wherein the iron salt is soluble in alcohol.

17. The method for producing a soft magnetic powder according to claim 16, wherein the iron salt is at least one selected from the group consisting of iron chloride, iron nitrate, and hydrates thereof.

18. The method for producing a soft magnetic powder according to any one of claims 14 to 17, wherein the water-soluble polymer and the surfactant have a ligand capable of forming a complex with Fe ions.

19. The water-soluble polymer is at least one selected from the group consisting of polyvinylpyrrolidone, polyvinyl alcohol, hydroxypropyl cellulose, poly(2-methyl-2-oxazoline), polyethyleneimine, polyacrylic acid and carboxymethyl cellulose. The method for producing a soft magnetic powder according to claim 18.

20. The method for producing a soft magnetic powder according to claim 18 or 19, wherein the surfactant is at least one selected from the group consisting of sodium polyoxyalkylene styryl phenyl ether phosphate, hexadecyltrimethylammonium bromide, and lauric acid diethanolamide.

21. The method for producing a soft magnetic powder according to any one of claims 14 to 20, wherein the metal alkoxide is at least one alkoxide selected from the group consisting of Si, Al, Ti and Zr.

22. The method for producing a soft magnetic powder according to any one of claims 14 to 21, wherein the solvent contains alcohol.

23. A magnetic core comprising the soft magnetic powder according to any one of claims 1 to 13 and a binder; Coil conductor and Including, the coil components.

24. Molding the soft magnetic powder according to any one of claims 1 to 13 to obtain a molded body; heat-treating the molded body to obtain a magnetic material; A method for producing a magnetic material, comprising:

Citation Information

Patent Citations

  • Magnetic material powder and magnetic material formed by using the same

    JP1997125111A

  • Soft magnetic material, dust core and method of producing soft magnetic material

    JP2006128663A

  • Powder magnetic core and method for manufacturing the same

    JP2011243830A

  • Dust core

    JP2012094804A

  • Powder-compact magnetic core, powder for magnetic core, and manufacturing method thereof

    JP2015088529A